Fabrication and Characterization of Transition Metal Dichalcogenides for the Production of Single Photon Emitters - Saber, Adriel F. S.; De Lima, Marcela R.; Oliveira, Suelen C. S.; Teodoro, Márcio D.; Barcelos, Ingrid D.; Moreira, Fernando M. A. (Anais do Workshop de Redes Quânticas (WQuNets); 2025: Anais do II Workshop de Redes QuânticasDO - 10.5753/wqunets.2025.8800, 2025)
This work aimed to fabricate and characterize a single-photon emitter based on WSe₂ monolayers conformed onto tungsten nanopillars via strain engineering. Optical measurements showed enhanced emission intensity and redshift in strained regions, features typical of single-photon emitters in nanopillar structures. However, photon anticorrelation yielded g²(0) = 0.67 ± 0.022, indicating classical behavior. The low purity may result from lack of encapsulation, multiple defects, and limited spectral filtering. Still, the results show potential for advancing these emitters in quantum technologies.